The Leri-Weill and Turner syndrome homeobox gene SHOX encodes a cell-type specific transcriptional activator - Rao, Ercole; Blaschke, Rüdiger Jörg; Marchini, Antonio; Niesler, Beate; Burnette, Michael H.; Rappold, Gudrun (Human molecular genetics, 2001)
Functional impairment of the human homeobox gene SHOX causes short stature and Madelung deformity in Leri-Weill syndrome (LWS) and has recently been implicated in additional skeletal malformations frequently observed in Turner syndrome. To enhance our understanding of the underlying mechanism of action, we have established a cell culture model consisting of four stably transfected cell lines and analysed the functional properties of the SHOX protein on a molecular level. Results show that the SHOX-encoded protein is located exclusively within the nucleus of a variety of cell lines, including U2Os, HEK293, COS7 and NIH 3T3 cells. In contrast to this cell-type independent nuclear translocation, the transactivating potential of the SHOX protein on different luciferase reporter constructs was observed only in the osteogenic cell line U2Os. Since C-terminally truncated forms of SHOX lead to LWS and idiopathic short stature, we have compared the activity of wild-type and truncated SHOX proteins. Interestingly, C-terminally truncated SHOX proteins are inactive with regards to target gene activation. These results for the first time provide an explanation of SHOX-related phenotypes on a molecular level and suggest the existence of qualitative trait loci modulating SHOX activity in a cell-type specific manner.
Gesehen am 07.04.2021